Small intestinal bacterial overgrowth and toll‐like receptor signaling in patients with non‐alcoholic fatty liver disease. Issue 1 (January 2016) - Kapil, Shweta; Duseja, Ajay; Sharma, Bal Krishan; Singla, Bhupesh; Chakraborti, Anuradha; Das, Ashim; Ray, Pallab; Dhiman, Radha K; Chawla, Yogesh
Abstract: Background and Aim: The pathogenesis of non‐alcoholic fatty liver disease (NAFLD) is multifactorial. There is sparse literature on the role of small intestinal bacterial overgrowth (SIBO) and toll‐like receptor (TLR) signaling in NAFLD. The present study evaluated the relationship of SIBO with expression of TLR signaling genes in patients with NAFLD. Methods: A total of 142 subjects composed of NAFLD ( n = 60, mean age 38.7 ± 10.4 years), chronic viral hepatitis (CVH) ( n = 32, mean age 39.5 ± 10.6 years), and healthy volunteers ( n = 50, mean age 36.56 ± 4.2 years) were enrolled in the study. Duodenal fluid was taken endoscopically in 32 prospective patients with NAFLD for evaluation of SIBO. Hepatic mRNA expression of TLR4, CD14, TLR2, NF‐κβ, and MD2 and protein expression of TLR4 and TLR2 were studied in 64 patients (NAFLD = 32, CVH = 32) by RT‐PCR and immunohistochemistry, respectively. Serum levels of TNF‐α, adiponectin, insulin, and endotoxins were also evaluated. Results: Small intestinal bacterial overgrowth was present in 12 (37.5%) out of 32 patients with NAFLD with Escherichia coli as the predominant bacterium. In comparison with those without SIBO, patients with SIBO had significantly higher endotoxin levels and higher CD14 mRNA, nuclear factor kappa beta mRNA, and TLR4 protein expression. Patients with NASH had significantly higher endotoxin levels and higher intensity of TLR4 protein expression in comparison with patients without NASH. Serum levels of TNF‐α, endotoxins, and insulin were significantly higher and of adiponectin lower in NAFLD in comparison with CVH and healthy volunteers. Conclusions: Our study provides the first direct evidence of role of SIBO and endotoxemia and its relation with TLR signaling genes and liver histology in patients with NAFLD.